A Pre-experimental Evaluation of a Structured Educational Program on Awareness of Mosquito-borne Diseases in Senior Secondary School Students in Punjab - Ramandeep Kaur; Sarabjeet Kaur; Sarbject Kaur; Simran Kumari; Sunita Devi; Satish Chandra Bansal; Samarjit Kaur (International Journal of Evidence Based Nursing And Practices, 2024)
Introduction: Mosquitoes constitute the most important single family of insects from the standpoint of human health. They are found all over the world. The four important groups of mosquitoes in India that are related to disease transmission are the Anopheles, Culex, Aedes, and Mansonia. Aims: The aims of the study are to assess the effectiveness of structured teaching program on knowledge regarding mosquito-borne diseases among students of senior secondary schools of Punjab. Methodology: A quantitative study method and a quasi-experimental design were employed. Sixty 12th-grade students were chosen using a non-probability sampling method. The study was conducted at selected government schools of Punjab. In this study, A self-structure knowledge questionnaire was implemented for data collection procedure. Pilot study was done for its clarity and finalized on similar subject. A pretest was administered, followed by the implementation of a structured educational program on mosquito-borne diseases. Subsequently, a post-test was conducted with the selected population. Results: The analysis of mean, standard deviation, and standard error mean for pre-test and post-test knowledge scores illustrates an advancement from an initial mean score of 10.23 to a final score of 13.93 after the intervention, indicating a notable improvement of 18.50%, thus validating the effectiveness of the structured teaching program (STP). The findings indicate a significant disparity between pre-test and post-test knowledge scores among 12th-grade students regarding mosquito-borne diseases, affirming the efficacy of the STP. Conclusion: The current study indicates that the STP successfully enhanced knowledge about mosquito-borne diseases among students in the 12th grade.
Keywords: Knowledge; human health; mosquito-borne diseases; non-probability sampling method; structured teaching program